La Normalización en México - Béjar Rivera, Luis José (Revista de Derecho, 2019)
Lately in Mexico, an interesting way and fairly useful for allowing an increase in thecitizen’s participation in the public administration has been the “normalización” (technicalrule making), which drifts between soft law and the general administrative decisions,proposing an important dialogue between the Public Administration and thecitizen, mainly to protect consumer’s rights, but also, as an instrument for the purposeof standardizing procedures and public acquisitions.The objective of this work precisely is to analyze the legal nature of these technicaldispositions, centered in the Official Mexican Norm (NOM), its administrative procedureof creation and the regulatory agencies.
Keywords: Administrative law; Technical Norm; Official Mexican Norm; Citizen’s participation; Administrative Procedure; Consumer’s rights